2021
DOI: 10.1016/j.heliyon.2021.e07205
|View full text |Cite
|
Sign up to set email alerts
|

Structural architecture of the Middle Niger Basin, Nigeria based on aeromagnetic data: An example of a non-volcanic basin

Abstract: The Middle Niger Basin is located within the west-central half of Nigeria, as a NW-SE trending Campano-Maastrichtian depo-centre which extends from the southern end of the Sokoto Basin west of Kainji reservoir southwestwards to the convergence of the Benue and Niger Rivers at Lokoja. The aeromagnetic anomaly data of the Middle Niger Basin was interpreted to characterize the structural architecture and depth to the magnetic basement of the basin. This is to expand the current knowledge of the region. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…This interpretation is corroborated by the low-frequency characteristics of these anomalies, indicative of the presence of igneous intrusive features within the basin's basement. Studies conducted by Kogbe et al (1983), Salawu et al (2020Salawu et al ( , 2021 provided additional supporting evidence for this interpretation, collectively confirming the distinctive nature of the Middle Niger Basin as an extensional sedimentary basin. This uniqueness is attributed to its formation within an extensional tectonic setting, where basement faults are rejuvenated because of the ascent of plutons.…”
Section: Tectonic Implications Of Magnetic and Gravity Anomalies In T...supporting
confidence: 53%
See 1 more Smart Citation
“…This interpretation is corroborated by the low-frequency characteristics of these anomalies, indicative of the presence of igneous intrusive features within the basin's basement. Studies conducted by Kogbe et al (1983), Salawu et al (2020Salawu et al ( , 2021 provided additional supporting evidence for this interpretation, collectively confirming the distinctive nature of the Middle Niger Basin as an extensional sedimentary basin. This uniqueness is attributed to its formation within an extensional tectonic setting, where basement faults are rejuvenated because of the ascent of plutons.…”
Section: Tectonic Implications Of Magnetic and Gravity Anomalies In T...supporting
confidence: 53%
“…The joint magnetic and gravity modeling of profile B-Bʹ was constraint by density values of sedimentary and volcanic rocks in adjacent Benue Trough (Table 1) as reported by Ajayi and Ajakaiye (1986). Furthermore, the density values from Stanton et al (2021) were used for the upper crust, lower crust, and the mantle in profile B-Bʹ (Table 1) while we used top basement depth values ranging from 1 to 2 km in the simulation (Ojo, 1990;Salawu et al, 2020Salawu et al, , 2021. According to Bouzid et al (2008), Brahimi et al (2018) and Deramchi (2016), 20 km may be employed to estimate top of the lower crust in the Trans-Saharan Belt.…”
Section: -D Modelingmentioning
confidence: 99%
“…In justification, recent aeromagnetic investigation of the Middle Niger Basin by Ref. 18 revealed that the basin is characterized by the absence of volcanic rocks. There is a regional trend (long wavelength) increase in the field northerly part of the RTP map.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…The basin has an average sedimentary pile of approximately 950 m from recent aeromagnetic results of Refs. 1,18 with two geographic subdivisions; the northern and southern segments. Four stratigraphic horizons in the northern part have been identified, which they include; the basal Bida Formation (conglomerate, sandstone) and Sakpe Ironstone of Campanian age and Enagi Formation (sandstone, siltstone, claystone) and Batati Ironstone of Maastrichtian age [19][20][21] .…”
Section: Geologic Settingmentioning
confidence: 99%
“…Towards the Southern and Northeastern part of the RTP map, the area is characterized by a relatively low magnetic intensity `value from -467.2 nT to -865.2 nT marked with blue colour. The closed contours represent high magnetic signatures linked to shallow structures such as contacts, fractures and intrusive bodies [41]. Reynold et al [40] and Opara [31] have associated the series of low magnetic closures with linear trends, which initiate shear/fault zones.…”
Section: Resultsmentioning
confidence: 99%